Effects of Classroom Observation of Parents to the Performance of Pupils - Ceria, Emerson T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study aimed to determine the effects of classroom observation of parents to the performance of pupils in Pandayan Elementary School for the school year 2019-2020. A descriptive research method was utilized in this study. A research – made instrument for pre-test and post-test aligned with the given learning competencies in the K to 12 Curriculum Guide in Grades 4 -6 was designed and undergone validity and reliability examination by peer-experts. After the validation from other Principals, the Division Research Chairperson has approved the instrument. The researcher also carried out a dry run before the actual pre-test and post-test assessment to the respondents. The gathered data from the tests were recorded and analyzed using Microsoft Excel and SPSS. The findings showed that the post-test scores have increased after the classroom observation of parents. In conclusion, there was a significant difference on the academic performance of pupils in Mathematics before and after classroom observation of parents.